Early Neutrophil Responses to Chemical Carcinogenesis Shape Long-Term Lung Cancer Susceptibility - Wculek, Stefanie K. (iScience, 2020)
Neoplastic transformation causing cancer is a key problem in tumor biology and can be triggered by exposure to environmental substances. We investigated whether the cellular composition of a tissue contributes to its predisposition to cancer upon a specific carcinogen. Neutrophils are important immune components involved in cancer progression, but their contribution to generation of transformed cells is elusive. Yet, neutrophil-released reactive oxygen species (ROS) can cause tissue damage, which potentially favors tumorigenesis. Here, we show that neutrophils contribute directly to neoplastic transformation by amplifying the genotoxicity of urethane in lung cells via ROS. Neutrophil-driven ROS-dependent DNA damage is timely restricted to urethane exposure and notably uncoupled from broad tissue damage or inflammation. Neutropenic granulocyte colony-stimulating factor (Gcsf)-knockout mice show reduced lung tumorigenesis, and forcing neutrophil recruitment only during urethane exposure rescues cancer incidence months later. This study shows that the time-restricted neutrophil response to carcinogens can impact the long-term tissue susceptibility to cancer.